IN VITRO ASSESMENT OF FUNGITOXICITY OF CINNAMON BARK OIL AGAINST ASPERGILLUS SPP. - NEERAJ SRIVASTAVA, (International Journal of Pharma and Bio Sciences, 2015)
The fungitoxic properties of vapours of essential oil extracted from Cinnamon (Cinnamomum zeylanicum Breyn) bark have been investigated against five species of Aspergillus viz. A. flavus Link, A. fumigatus Fresenius, A. nidulans (Eidam) Wingate, A. niger van Tiegham and A. terreus Thom, causing biodeterioration of paper manuscripts in Gorakhpur. The fungitoxicity was determined in vitro as minimum inhibitory concentration (MIC), minimum lethal concentration (MLC) and inoculum density sustained at MIC and higher doses (fungicidal or fungistatic nature). It is concluded that this oil is effective against all the five selected species of Aspergillus and can be recommended for further in vivo investigations against Aspergillus spp. It is also suggested that the oil should be tested in vitro and in vivo against species of Aspergillus causing diseases in birds, animals and humans too, in order to explore the possibility of their use as a chemotherapeutic agent.